Hydrogeochemistry and Genetic Fluids of the Non-Volcanic Geothermal System, Hot Spring in Tehoru District, Maluku Province, Indonesia - Yusuf Mehdi Khairi Toisuta; Agus Didit Haryanto; Johanes Hutabarat (Geoid, 2026)
Maluku is one of the provinces in Indonesia with non-volcanic geothermal potential, as it is geographically located at the intersection of three active tectonic plates, the Eurasian, Pacific, and Indo-Australian. This supports the emergence of geothermal manifestations without volcanic activity. Tehoru is one of many areas with non-volcanic geothermal potential in Indonesia, located in the province of Maluku, Central Maluku Regency, Tehoru District. In this area, geothermal phenomena such as hot springs, mud pools, and fumaroles have been discovered. Based on anion-cation hydrogeochemical analysis and supported by the results of stable isotope analysis of δ18O and δ2H, this research examines 4 samples of hot springs and 1 sample of a cold spring. Overall, these samples originate from heated meteoritic water, and the fluid interacts with rocks before reaching the surface as phreatic water. APTHR-2 appears in a state of full equilibrium, APTHR-1 and APTHR-3 appear in a state of partial equilibrium, while APTHR-4 and ADTHR-1 appear on the surface in a state of immature waters. The estimated reservoir temperature ranges from 161 to 194°C, indicating that the Tehoru geothermal system is a medium-enthalpy geothermal system. This is supported by the lithological conditions in the study area, which consist of metamorphic and altered rocks. Based on these analysis results, it can be confirmed that there is no volcanic activity in the Tehoru Geothermal Area, Maluku, Indonesia. The type of geothermal system in Tehoru is assumed to be a fractured system or heat sweep system.